Shaping food environments to support sustainable healthy diets in low and middle-income countries - Kumar, Shalander; Das, Abhishek; Kasala, Kavitha; Ridoutt, Bradley George (Frontiers in Sustainable Food Systems, 2023)
The global ambitions to end hunger, achieve food security and improved nutrition, and promote sustainable agriculture demand a complex transition of the current food environments for enabling sustainable healthy diets. The food environments in Low and Middle-Income Countries (LMICs) have been experiencing rapid and dynamic transitions across the globe, necessitating a system-level thinking and systemic approach to understand opportunities for improvement. There is a need for valid, reliable measures of food and nutrition environments for reorienting thinking and data collection toward determinants of food demand, especially the food environment components, which are critical to understand the transforming food systems. Food environment transformations are urgently required to provide consumers with more affordable and nutritious diets capable of meeting social and environmental challenges. In the present perspective, we aim to provide insights on prioritizing research on understanding and designing evidence based inclusive food environments which is crucial for promoting long-term food system innovations that are economically, socially, and environmentally sustainable and, above all, contribute to sustainable healthy diets.